Ruqyah Jaranan And Its Resistance On The Dominant Culture - Muhammad Nikmal Anas Alhadi Anas (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2023)
This paper discusses how Ruqyah Jaranan, a cultural event in East Java, is constructed as a resistance to the existing culture. It was typical that resistance appears from the weak side to the strong side. This case shows a resistance culture that was born from the strong to the weak culture. It specifically talks about the way Ruqyah Jaranan emerged in Kedawung Jember as a way to change the nature of the good young generation in that village. This paper argues that this event is an attempt from a particular people in dealing with what so called as “good young generation”. But the value of the culture has negotiated with the way the society in that village articulated the nature of the good young generation. This event has implications to shape the religiosity and morality of the young generation as behavior in daily life.